Legal Analysis of Human Rights Protection within Smart City Policy Implementation in Indonesia - Saleha, Dwi; Djuhrijjani, Djuhrijjani; Awaliyah, Reni; Furqon, Wahyul; Sudarmanto, Eko (The Easta Journal Law and Human Rights, 2025)
The implementation of smart city policies in Indonesia represents a major step toward integrating digital technologies into urban governance to improve public services, environmental sustainability, and citizen engagement. However, the rapid adoption of digital systems also raises concerns regarding the protection of human rights—particularly privacy, data security, freedom of expression, and non-discrimination. This study employs a normative legal analysis to examine Indonesia’s legal framework for safeguarding human rights within smart city policy implementation. Using primary and secondary legal materials, including the 1945 Constitution, Law No. 39 of 1999 on Human Rights, the Electronic Information and Transactions (ITE) Law, and the Personal Data Protection Law (Law No. 27 of 2022), the research evaluates their coherence and adequacy in regulating digital governance. The findings reveal that while Indonesia has established a fundamental legal basis for human rights protection, gaps persist in enforcement, institutional coordination, and public awareness. Smart city initiatives often prioritize technological efficiency over human rights safeguards, resulting in privacy violations, digital inequality, and limited accountability. The study concludes that integrating a human rights–based approach (HRBA)—focusing on participation, accountability, non-discrimination, and transparency—is essential for ensuring that smart city development aligns with constitutional and international human rights standards.